The Effects of Film Thickness and Substrate Resistivity on Corrosion of Iron Thin Films. (7th July 2017) - Sapiro, David; Feng, Ruishu; Webler, Bryan; Ziomek-Moroz, Margaret; Ohodnicki, Paul R
Abstract : This study investigated the corrosion behavior of Fe films with different thicknesses in NaCl solution. It has been reported that nanocrystalline metal thin films are more corrosion resistant than their coarser bulk counterparts, but the effect of thickness is not well characterized. Polarization curves were generated for three iron thin films with thicknesses of 10, 20, and 100 nm and bulk iron in aerated 3.5 wt% NaCl solution at 24 ˚C. All films were deposited on silica substrates, and 20 and 100 nm films were also deposited on silica substrates with a Pt conductive under-layer. The resistivity/conductivity of the samples were measured using a four point probe, and the effects of film and substrate resistivity on corrosion were addressed by comparing polarization curves of thin films with and without the Pt conductive layer. The extent of film corrosion was spatially varied and the variation in localized electrochemical response was measured using scanning vibrating electrode technique (SVET). The corroded films were also characterized by optical microscopy.